1998
DOI: 10.1099/00221287-144-9-2531
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of the haemocin locus of Haemophilus influenzae type b and assessment of the role of haemocin in virulence

Abstract: The bacteriocin haemocin (HMC) is produced by most type b strains of Haemophilus influenzae, including strains determined to be genetically diverse, and is toxic to virtually all non-type b strains of H. influenzae, both encapsulated and non-encapsulated. Examination of the deduced amino acid sequences of several genes upstream of the previously identified HMC immunity gene (hmcl) revealed several features common to class II bacteriocins of certain Gram-positive bacteria. Mutagenesis of the open reading frame … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2000
2000
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Although in vitro experiments suggest that exchange of encapsulation loci is possible, the clonal population structure of these bacteria suggests that this is uncommon. Additionally, we found that hmcA (19), the structural gene encoding the type b-specific bacteriocin haemocin was absent in all non-type b encapsulated isolates, suggesting that none of these strains was related to Hib (data not shown).…”
Section: Vol 71 2003 Non-type B Encapsulated H Influenzae Virulencmentioning
confidence: 86%
“…Although in vitro experiments suggest that exchange of encapsulation loci is possible, the clonal population structure of these bacteria suggests that this is uncommon. Additionally, we found that hmcA (19), the structural gene encoding the type b-specific bacteriocin haemocin was absent in all non-type b encapsulated isolates, suggesting that none of these strains was related to Hib (data not shown).…”
Section: Vol 71 2003 Non-type B Encapsulated H Influenzae Virulencmentioning
confidence: 86%
“…The Rd genome is estimated to be 270 kb smaller than that of virulent type b strain Eagan (6). Capsule type b (24), pili (hif) (44), tryptophanase (tna) (27), and haemocin (hmc) (30) genes are present in Hib strains and are not found in Rd. The cap b, hif, and tna loci are each flanked by direct repeats.…”
mentioning
confidence: 99%
“…E9 is similar to the H. influenzae type b strain E1a hemocin gene (hmcD) and has a GϩC content that is much lower than the 38% reported for H. influenzae strain Rd KW20 (10) (hereafter referred to as Rd). Interestingly, the entire hmc E1a locus has a significantly lower GϩC content (20), suggesting that it represents a genomic region acquired by H. influenzae encapsulated and nonencapsulated strains from an unrelated source. A small portion of F2 is similar to srmB of Rd (10), which is related to D-E-A-D box helicases (26), while most of it is related to a Neisseria meningitidis MC58 adhesin (32) and the Moraxella catarrhalis UspA2 and UspA2H proteins.…”
mentioning
confidence: 99%